A case of peritoneal dialysis-associated peritonitis caused by Sphingomonas paucimobilis - Jae Un Lee; Joong Keun Kim; So Hee Yun; Moon Sik Park; Na Eun Lee; In O Sun; Kwang Young Lee (The Korean Society of Nephrology, 2013)
Sphingomonas paucimobilis is an aerobic Gram-negative bacillus found in soil and water. Knowledge regarding the role of this infectious agent is limited because it is rarely isolated from human material. Furthermore, it is an unusual pathogen in cases of peritoneal dialysis (PD)-associated peritonitis. The clinical courses and outcomes of peritonitis caused by S. paucimobilis are variable. Whereas some patients were cured with appropriate antibiotic therapy, others required catheter removal. Cases of PD-associated peritonitis caused by S. paucimobilis have been reported worldwide, and there was a case report of coinfection with S. paucimobilis and Chryseobacterium indologenes in Korea. However, there has been no case caused by S. paucimobilis as a single pathogen. We report a case of PD-associated peritonitis due to S. paucimobilis in which the patient recovered after catheter removal.